Penatalaksanaan Fisioterapi Pada Kasus Post Orif Fraktur Cruris 1/3 Distal Sinistra Di RSUD Salatiga - Akbar, Ega Doviana; , Dwi Kurniawati, SST.FT, M.Kes (2015)
Background: Fracture cruris 1/3 distal sinistra is a break of continuity of bone tissue structures that occur in the tibia and fibula bones are located in the lower 1/3 of the left leg. While ORIF is an internal mounting plate and screw fixation form. The issues that arise include: the presence of pain arises in the former installation operation ORIF, the LGS limitations on the left ankle, decreased muscle strength, and the presence of edema in the left ankle. To solve the problems that arise, physiotherapy modalities used are infra red and exercise therapy in the form of forced passive exercise, free of active exercise, as well as active resisted exercise. The purpose of these modalities is to reduce pain, increase LGS, reduce edema and improve muscle strength. Methods: This research paper uses a case study method salvage therapy six times Results: Examination of reduced pain seen from the results of measurements with VAS, reduced edema examination with midline, LGS increases with goneometer examination and examination of muscle strength increased with Manual Muscle Testing. Conclusions: The decrease of the management of pain, the addition of LGS, decrease edema, and increase muscle strength. On the issues that arise in the case of post ORIF fracture of the left distal 1/3 cruris using Infra red and exercise therapy.